2012
DOI: 10.3390/rs4082373
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Four Models to Estimate Chlorophyll-a Concentration in Case-2 Waters Using MODerate Resolution Imaging Spectroradiometer (MODIS) Imagery

Abstract: Abstract:The occurrence and extent of intense harmful algal blooms (HABs) have increased in inland waters during recent decades. Standard monitor networks, based on infrequent sampling from a few fixed observation stations, are not providing enough information on the extent and intensity of the blooms. Remote sensing has great potential to provide the spatial and temporal coverage needed. Several sensors have been designed to study water properties (AVHRR, SeaBAM, and SeaWIFS), but most lack adequate spatial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing techniques have been extensively used for monitoring chl-a in aquatic systems [4,[8][9][10]. The advantages of using remote sensing techniques to monitor chl-a are: (1) the geographical coverage of satellite images, which provide information about the entire aquatic system; (2) remote sensing, which allows us to obtain information from inaccessible places; and (3) historical satellite images, which allow the inference of water quality information from the past records [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods for estimating chl-a concentration in different turbid waters (Case 2) with remote sensing have been investigated [4][5][6][7][8][9][10][11][12]. Many studies have suggested that remote spectroscopic measurements from the Moderate Resolution Imaging Spectroradiometer (MODIS) should be used to estimate chl-a concentrations in Case 2 waters through empirical and semi-empirical algorithms [4,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional monitoring methods consist of collection of field samples, laboratory analysis, and manual cell counts. These methods are time-consuming, labor intensive and costly [8]. Efficient alternative methods should be developed in order to improve the monitoring of CHABs and remote sensing has been proved as a valuable tool for this application [9].…”
Section: Introductionmentioning
confidence: 99%
“…Performance of the AM was evaluated utilizing cross-validation using several statistical evaluation indices and a confusion matrix using an independent semi-quantitative database. We also used the same databases (continuous and ordinal) to compare performance of the AM to that of three other models originally developed to estimate Chl-a in inland waters (the Floating Algae Index (FAI), Kahru model, and APProach by ELimination (APPEL)) [13,22,24].…”
mentioning
confidence: 99%